Locus‐of‐care disparities in end‐of‐life care intensity among adolescents and young adults with cancer: A population‐based study using the IMPACT cohort. Issue 2 (15th September 2021) - Coltin, Hallie; Rapoport, Adam; Baxter, Nancy N.; Nagamuthu, Chenthila; Nathan, Paul C.; Pole, Jason D.; Momoli, Franco; Gupta, Sumit
Abstract : Background: Adolescents and young adults (AYAs) with cancer may experience elevated rates of high‐intensity end‐of‐life (HI‐EOL) care. Locus‐of‐care (LOC) disparities (pediatric vs adult) in AYA end‐of‐life (EOL) care are unstudied. Methods: A decedent population‐based cohort of Ontario AYAs diagnosed between 1992 and 2012 at the ages of 15 to 21 years was linked to administrative data. The authors determined the prevalence and associations of a composite outcome of HI‐EOL care that included any of the following: intravenous chemotherapy within 14 days of death, more than 1 emergency department visit, more than 1 hospitalization, or an intensive care unit (ICU) admission within 30 days of death. Secondary outcomes included measures of the most invasive EOL care (ventilation within 14 days of death and ICU death) and in‐hospital death. Results: There were 483 decedents: 60.5% experienced HI‐EOL care, 20.3% were ventilated, and 22.8% died in the ICU. Compared with patients with solid tumors, patients with hematological malignancies had the greatest odds of HI‐EOL care (odds ratio [OR], 2.3; 95% confidence interval [CI], 1.5‐3.4), ventilation (OR, 4.7; 95% CI, 2.7‐8.3), and ICU death (OR, 4.4; 95% CI, 2.6‐4.4). Subjects treated in pediatric centers versus adult centers near death (OR, 2.4; 95% CI, 1.2‐4.8) and those living in rural areas (OR, 2.1; 95% CI, 1.1‐3.9) were more likely to experience ICU death. Conclusions: AYAs with cancer experience high rates of HI‐EOL care, with patients in pediatric centers and those living in rural areas having the highest odds of ICU death. This study is the first to identify LOC‐based disparities in EOL care for AYAs, and it highlights the need to explore the mechanisms underlying these disparities. Abstract : In this population‐based linkage study of adolescent and young adult cancer decedents, patients treated in pediatric settings near death experience disproportionate rates of intensive end‐of‐life care in comparison with adult settings. Other risk factors are hematological malignancies and rural living.